(untitled) (ENTHYMEMA, 2019)
Rouputuan is a 17th-century Chinese erotic novel published under a pseudonym but traditionally attributed (though not without dispute) to the versatile writer, poet, publisher, essayist, painter, as well as author and theatrical impresario, Li Yu (1610-1680). The novel is remarkable also for its refined style, its beautiful narrative structure, and its alternance between the uses of an amiguous and sarcastic irony and a faithful adherence to the Buddhist belief and doctrine. Rouputuan has long been the object of censorship by government censorship during the last imperial dynasty, and it is mostly considered a pornographic work because it doesn’t seem to offer an explicit denunciation of the corrupt customs of the time, as it is found in other erotic novels such as the Jinpingmei. The Rouputuan seems to have creating a peculiar system of ideological values that is conveyed by a double code of communication: on the one hand, it uses the vernacular language, linked to the oral tradition, and therefore more easily conveyed; on the other hand it has an important figurative apparatus, aimed at giving greater emphasis and effectiveness to the described subject. This is strictly linked to the Chinese social context that encouraged a symbiotic connection between calligraphy, poetry and painting which was one of the basic characteristics of the literati formation. This two-part contribution intends to examine the problems related to the translation of the novel also in reference to its iconographic apparatus, to reflect on the aesthetic and literary choices to define the (cultural) boundaries in late imperial China between licit and illicit, eros and pornography, moralistic repression and evasion, vulgarity and artistic aspiration, orthodoxy and heterodoxy.